Bio-inspired incorporation of functionalized graphene oxide into carbon nanotube fibers for their efficient mechanical reinforcement - Kim, Young-Jin; Park, Junbeom; Yang, Cheol-Min; Jeong, Hyeon Su; Kim, Seung Min; Han, Sang Woo; Yang, Beomjoo; Kim, Young-Kwan (Pergamon Press Ltd., 2019)
An efficient strategy for the enhancement of mechanical properties of carbon nanotube (CNT) fibers is developed using functionalized graphene oxide with a quaternary ammonium (QA) group (QA-FGO). QA-FGO is designed to induce the p-cation interaction, one of the strongest interactions in living systems, with CNT fibers. Based on the strategy, the tensile strength (58 MPa), specific strength (0.49 N/tex), modulus (2.5 GPa) and toughness (1.1 MJ/m(3)) of CNT fibers are enhanced to 409 MPa, 0.65 N/tex, 13.4 GPa, and 10.1 MJ/m(3), respectively. The reinforcement mechanism is systematically demonstrated with experimental and theoretical approaches.